Cumulative mild head injury in contact sport: a comparison of the cognitive profiles of rugby players and non-contact sport controls with normative data - Bold, Lisa Clare (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
This study investigates the effects of cumulative mild head injury on the cognitive functioning of elite rugby players. A comprehensive battery of neuropsychological tests was administered to top national (Springbok) rugby players (n=26), national Under 21 rugby players (n= 19), and a non-contact sport control group of national hockey players (n=21). The test results of the Total Rugby group (Springbok Rugby and Under 21 Rugby players), the Under 21 Rugby group, the hockey controls, and the Total Rugby and Under 21 Rugby forward and backline players respectively, were each compared with established normative data. Results showed significant differences in the direction of a poorer performance relative to the norms for the Total Rugby and Under 21 Rugby groups, and for the Total Rugby Forwards and Under 21 Rugby Forwards, on tests sensitive to the effects of diffuse brain damage. On the other hand, the Hockey Control group and the Total Rugby Backs and Under 21 Rugby Backs tended to perform within the normal range or better than the norm on some tests. These results confirm the hypothesis that rugby players, and the forward players in particular, are at risk of adverse cognitive effects consequent on cumulative mild head injury. The theoretical implications are that the aggregate effects of multiple exposures to mild head injuries in the rugby players served to reduce their brain reserve capacities and acted as a threshold-lowering influence associated with symptom onset.
Keywords: Head -- Wounds and injuries -- Psychology; Neuropsychological tests; Head -- Wounds and injuries; Sports injuries -- Psychological aspects